2007
DOI: 10.1016/j.cognition.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Language-specific and universal influences in children’s syntactic packaging of Manner and Path: A comparison of English, Japanese, and Turkish

Abstract: Different languages map semantic elements of spatial relations onto different lexical and syntactic units. These crosslinguistic differences raise important questions for language devel- opment in terms of how this variation is learned by children. We investigated how Turkish-, English-, and Japanese-speaking children (mean age 3;8) package the semantic elements of Manner and Path onto syntactic units when both the Manner and the Path of the moving Figure occur simultaneously and are salient in the event depic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
172
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(196 citation statements)
references
References 24 publications
19
172
3
2
Order By: Relevance
“…These differences are already in place as early as three years of age in Path vs. Manner languages (Allen, Özyürek, Kita, Brown, Furman, Ishizuka & Fujii, 2007;Slobin, 1996Slobin, , 2003cf. Naigles, Eisenberg, Kako, Highter & McGraw, 1998;Papafragou, Massey & Gleitman, 2002, 2006 and affect conjectures about the meanings of novel verbs in both children and adults (Naigles & Terrazas, 1998;Papafragou & Selimis, 2007).…”
Section: Nonlinguistic Representations Of Motion Eventsmentioning
confidence: 99%
“…These differences are already in place as early as three years of age in Path vs. Manner languages (Allen, Özyürek, Kita, Brown, Furman, Ishizuka & Fujii, 2007;Slobin, 1996Slobin, , 2003cf. Naigles, Eisenberg, Kako, Highter & McGraw, 1998;Papafragou, Massey & Gleitman, 2002, 2006 and affect conjectures about the meanings of novel verbs in both children and adults (Naigles & Terrazas, 1998;Papafragou & Selimis, 2007).…”
Section: Nonlinguistic Representations Of Motion Eventsmentioning
confidence: 99%
“…We asked children and adults to produce short narratives as they talked about 10 animated short movies (used in Allen et al, 2007;Kita et al, 2007;and Ö zyürek et al, 2005). The movies contain motion events in which simultaneously occurring manner and path are both salient.…”
Section: Present Studymentioning
confidence: 99%
“…Note that the data for the English-and Turkish-speaking adults and 3-year-olds come from the same data set reported in Allen et al (2007). However, the criteria for using the data of individual participants, as well as the units of analysis used, are somewhat different across the two studies, with resulting slight differences in the findings reported.…”
Section: Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Iconic gesture in normal language and word searching conditions: A case of conduction aphasia. Published in International Journal of 15(5),[524][525][526][527][528][529][530][531][532][533][534] children (Allen, Özyürek, Kita, Brown, Furman, Ishizuka & Fujii. 2007;Özyürek, Kita, Allen, Brown, Furman, & Ishizuka, 2008).…”
mentioning
confidence: 99%